Design and development of motoraise grinding valve for motorcycle engine - Abdul Hadi, Shamsul Kamar (2012)
This report shows the design and development of motoraise grinding valve for motorcycle engine. The objective of the report is to design and development a motoraise grinding valve for motorcycle engine. Design generation is showed and solid three dimensional structures modelling of the motoraise grinding valve was developed with computer aided design software. This report also explains the fabrication process that is needed for this project. Material that is being used in this project is galvanize iron sheet metal and mild steel bar, shaft and hollow shaft. The problems encountered during completion of this project are also show in the report. An idea of improvement for the motoraiser grinding valve is also provided to further improve the motoraiser grinding valve. The expected result for this project can solve the entire stated problem statement.